An extensive simulation research on AODV in mobile ad hoc environment - Poluboyina, Lavanya; Kumar Reddy V, Siva; Prasad A, Mallikarjuna (International Journal of Engineering and Technology, 2018)
Technical advancements in wireless technology and portable devices leading to new features in wireless communication networks, mobile ad hoc networks (MANETs) are a kind of them. MANETs are, containing autonomous mobile nodes (nodes with special abilities) a class of multihop wireless networks where two distant nodes can communicate with each other without a centralized administration or an underlying network infrastructure. Networks having such features find applications like where there is a need for an instantaneous temporary network to handle emergency situations. On the other hand, being dynamic networks with time to timevarying topologies MANETs are placing the challenges in routing the data packets in the network. This paper presents an extensive simulation work done on the most prominent ondemand routing protocol i.e., ad hoc on demand distance vector routing protocol (AODV) is for a set of performance evaluation parameters by varying a set of various network parameters.Â